Education for Family Planning Acceptors to Use IUD Contraception at the Cikeusik Pandeglang Community Health Center - Albahra, Albahra; Fathiyati, Fathiyati; Siswosuharjo, Partono (JOURNAL EDUCATIONAL OF NURSING(JEN), 2024)
This study aims to determine the factors associated with family planning acceptors' reluctance to use IUD contraception. The type of research used is cross sectional research. The sample in this study was 99 respondents. The results of the research obtained that the age value with reluctance to use IUD family planning P Value = 0.17 with a value of ɑ=0.05, parity with a value of P Value = 0.065 with a value of ɑ=0.05, education value P Value = 0.958 with a value of ɑ= 0.05, knowledge value P Value = 0.975 with a value of ɑ=0.05, so Ho is accepted meaning there is no relationship between age, parity, education and knowledge and reluctance to use IUD family planning. Based on the data obtained from the research results, it was found that all of the four variables of age, parity, education and knowledge studied had no relationship to the reluctance to use IUD contraception. Through this research, it is hoped that family planning acceptors will increase their knowledge, especially about IUD contraception, and be more careful and precise in choosing a family planning contraceptive method that is tailored to the acceptor's condition and understand how to use it, the benefits and side effects in increasing a happy and prosperous family